Pengaruh Persistensi Laba, Book Tax Differences, Investment Opportunity Set dan Struktur Modal Terhadap Kualitas Laba dengan Konservatisme Akuntansi Sebagai Variabel Moderasi (Studi Empiris pada Perusahaan Jasa yang Terdaftar di BEI Periode 2015-2017) - Fathin Ulfatul Ashma’; Evi Rahmawati (Universitas Muhammadiyah Yogyakarta, 2019)
This research aims to examine the Effect of Earnings Persistence, Investment Oppotunity Set, Book tax differences and Capital Structure on Earnings Quality with Accounting Conservatism as Moderating Variable. The population in this research are service companies listed in Indonesia Stock Exchange for the period 2015-2017. The data used in this study are secondary data in the form of quantitative data from the financial statements of service companies listed on the Indonesia Stock Exchange (IDX) in 2015-2017. In this research the method used for sampling is using the purposive sampling method and obtained a sample of 268 samples. Data obtained from the Indonesia Stock Exchange (IDX) and the website www.idx.co.id, the data analyzed in this study are processed from annual reports and company financial statements. Based on the analysis that has been done, the results show that the earnings persistence and Investment Opportunity Set does not affect the quality of earnings. Book Tax Differences has a negative effect on earnings quality. Capital structure has a positive effect on earnings quality. Book tax differences has a effect on earnings quality with accounting conservatism as a moderating variable.